Report of the Task Force on Connectivity and Promotion of Trade and Investment in NE States - Planning Commission (Planning Commission Government of India, 2006)
The Task Force Report on Connectivity and Promotion of Trade & Investment in North-East India (2006) provides a comprehensive roadmap for enhancing infrastructure and economic development in the region. The report identifies critical gaps in connectivity due to geographical isolation and substandard infrastructure, proposing priority investments in highways, railways, air transport, and inland waterways to improve logistics, trade, and tourism. Key recommendations include constructing new all-weather roads, doubling rail lines, upgrading airports, and modernizing inland water transport facilities. The report emphasizes leveraging the region’s natural resources—hydro-power, minerals, and biodiversity—and promoting entrepreneurship and industrial development, including bamboo processing and horticulture. Measures to reduce Aggregate Technical & Commercial (AT&C) losses in electricity distribution are highlighted, alongside proposals for strengthening financial and regulatory frameworks to facilitate investment. The total financial requirement for infrastructure and trade-enhancing projects is estimated at ₹46,452 crores, with funding gaps addressed through strategic planning, public-private partnerships, and the creation of an Infrastructure Development Fund. Implementation of these recommendations is expected to significantly improve trade, investment, and energy reliability, integrating the North-East more effectively into national and international economic frameworks.
Planning Commission Government of India October, 2006
Keywords: North-East India; Connectivity; Trade Promotion; Infrastructure Development; Highways; Railways; Air Transport; Inland Water Transport; Power Supply; AT&C Losses; Investment Opportunities; Public-Private Partnerships